ChemInform Abstract: Biomimetic Approach for the Synthesis of N, N′‐Diarylsubstituted Formamidines Catalyzed by β‐Cyclodextrin in Water. Issue 8 (1st March 2013) - Patil, Dipak R.; Dalal, Dipak S.
Abstract A facile procedure employing β‐cyclodextrin as reusable catalyst allows the synthesis of the title compounds (III) via reaction of triethylorthoformate with anilines.